2021
DOI: 10.4103/jehp.jehp_1313_20
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to distress among school and college-going adolescents during COVID-19 Lockdown: A cross-sectional study conducted in Sibi Balochistan, Pakistan

Abstract: BACKGROUND: Due to the COVID-19 pandemic, many countries have implemented nationwide lockdowns. While this leads to a decrease in disease transmission, there is a concurrent increase in the levels of psychological distress. To estimate the levels of psychological distress in school- and college-going adolescents currently under lockdown and to determine the factors associated with this psychological distress. MATERIALS AND METHODS: A cross-sectional study conducted in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…COVID-19 engendered a plethora of uncommon negative psychological responses, including COVID-19 stress, fatigue, mental health problems, and negative affect [ 58 , 61 , 68 , 76 , 90 , 105 ]. COVID-19 stress, as a new negative psychological response that emerged during the pandemic [ 65 ], may have been for most youth an adaptive response that prompted them to take precautions (e.g., frequent hand washing and social distancing) to protect themselves from the virus.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 engendered a plethora of uncommon negative psychological responses, including COVID-19 stress, fatigue, mental health problems, and negative affect [ 58 , 61 , 68 , 76 , 90 , 105 ]. COVID-19 stress, as a new negative psychological response that emerged during the pandemic [ 65 ], may have been for most youth an adaptive response that prompted them to take precautions (e.g., frequent hand washing and social distancing) to protect themselves from the virus.…”
Section: Discussionmentioning
confidence: 99%
“…They evaluate the intensity, duration, and frequency of PA. In the quantitative analysis, they adopt International PA Questionnaire (IPAQ) [ 26 ], the Pediatric Functional Activity Brief Scale (PFABS) [ 16 , 18 ], the Leisure-Time Exercise Questions [ 25 ], questions from the Youth Risk Behavior Surveillance Survey [ 29 ], and the PA questionnaire for children (PAQ-C) [ 21 , 27 ]. As for mental health, most of the studies evaluate people’s anxiety, depression, and other negative emotions (such as tension, depression, anger, fatigue, confusion, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…As for mental health, most of the studies evaluate people’s anxiety, depression, and other negative emotions (such as tension, depression, anger, fatigue, confusion, etc.) through the State-Trait Anxiety Inventory for state-Anxiety for Children(STAIC S-Anxiety) [ 28 ], the 10-item Positive and Negative Affect Schedule for Children (PANAS-C) 1 , Profile of Mood States (POMS) [ 19 , 26 ], the General Anxiety Disorder 7-Item(GAD-7) for anxiety [ 16 , 18 ], Patient Health Questionnaire 9-Item (PHQ-9) for depression [ 16 , 18 ], the Strengths and Difficulties Questionnaire (SDQ) [ 29 ], World Health Survey [ 24 ], Behavior Assessment System for Children (BASC-3) [ 22 ], Middle Years Development Instrument (MDI) [ 22 ], Kessler‑10 (K10) [ 25 ], the Rosenberg self-esteem scale [ 21 ], and the 20-item Center for Epidemiologic Studies Depression [ 20 ]. Besides, Xiao et al [ 19 ] also study the correlation between PA and conflicts with parents, which can reflect the influence on the mental health of children and adolescents to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, there has been bereavement, isolation, loss of income, and increasing mental health conditions or exacerbating existing ones. [ 1 2 3 ] Seventy two percent of respondents for a poll conducted in late March 2020 reported that their lives were noticeably disrupted since the pandemic began, which was a 32% increase since the same poll conducted two weeks prior. [ 4 ] Any mental illness (AMI) is defined as a mental, behavioral, or emotional disorder and according to the National Institute of Health report from 2020, young adults aged 18–25 years had the highest prevalence of AMI (30.6%) compared with adults aged 26–49 years (25.3%) and aged 50 and older (14.5%).…”
Section: Introductionmentioning
confidence: 99%